Development Period of Forensic Importance Calliphoridae (Diptera: Brachycera) in Urban Area Under Natural Conditions in Manaus, Amazonas, Brazil - Barros-Souza, Alex Sandro; Ferreira-Keppler, Ruth Leila; Agra, Daniela de Brito (EntomoBrasilis, 2012)
In order to describe the development period of forensically-important Calliphoridae species (Diptera: Brachycera) under natural conditions in Manaus, Amazonas, Brazil, two experiments were carried out at Campus II of National Institute for Amazon Research (INPA), Manaus, Amazonas, one in the rainy season and the other one in the less rainy season. Pig carcasses (25kg each) were used as attractive to oviposition of the blowflies. Calliphoridae females were collected and the eggs were placed into containers with ground beef. The reared species and development time from egg to adult (in days) in the rainy season and less rainy season, respectively, were: Chrysomya albiceps (Wiedemann) 14.5 days and 9.4 days, C. megacephala (Fabricius) 10.7 and 9.4, Hemilucilia segmentaria (Fabricius) 11.5 and 10.7, Lucilia eximia (Wiedemann) 19.7 and 14.3 and Paralucilia paraensis (Mello) reared only in the less rainy season with 11.8 days. This is a first record of the development time of P. paraensis. Período de Desenvolvimento sob Condições Naturais de Espécies de Calliphoridae (Diptera: Brachycera) de Importância Forense em Área Urbana, Manaus, Amazonas, Brasil Resumo. Para descrever o tempo de desenvolvimento dos imaturos de Calliphoridae sob condições naturais, dois experimentos foram realizados no Campus II do Instituto Nacional de Pesquisas da Amazônia (INPA), Manaus, Amazonas, um na estação chuvosa e o outro na estação menos chuvosa. Cadáveres de porcos domésticos (25kg cada) foram utilizados como substrato atrativo para a ovipostura dos califorídeos. Fêmeas grávidas de Calliphoridae foram coletadas e os ovos foram transferidos para potes plásticos contendo placas de Petri com carne bovina moída. As espécies criadas, com respectivo tempo de desenvolvimento de ovo a adulto (em dias), na estação mais chuvosa e menos chuvosa, foram: Chrysomya albiceps (Wiedemann), 14,5 e 9,4 dias, Chrysomya megacephala (Fabricius), 10,7 e 9,4, Hemilucilia segmentaria (Fabricius), 11,5 e 10,7 Lucilia eximia (Wiedemann) 19,4 e 14,3 e Paralucilia paraensis (Mello), 11,8 dias, essa criada somente na estação menos chuvosa. Este é o primeiro registro do tempo de desenvolvimento de P. paraensis.